How do functional traits influence tree demographic properties in a subtropical monsoon forest?. (10th October 2022) - He, Pengcheng; Lian, Juyu; Ye, Qing; Liu, Hui; Zheng, Yi; Yu, Kailiang; Zhu, Shidan; Li, Ronghua; Yin, Deyi; Ye, Wanhui; Wright, Ian J.
Abstract: Functional traits are good predictors of plant responses and adaptations to ever‐changing environments. However, forecasting forest community dynamics is challenging because the relationships among different tree demographic properties (growth, mortality and recruitment) and how functional traits are associated with tree demography remain largely unknown. Here, in a 20‐ha subtropical forest permanent plot, we quantified the rates of tree growth, mortality and recruitment across 53 dominant tree species (diameter at breast height; DBH ≥ 1 cm) from 2005 to 2020. Functional traits that are closely related to plant photosynthesis, nutrients, hydraulics and drought tolerance were measured. We found that tree growth rate (GR) varied independently from rates of tree mortality and recruitment. Hydraulic conductivity was positively correlated with GR (explaining 27% variation—the strongest relationship observed) whereas wood density was negatively correlated with GR. Leaf life span was negatively related to tree mortality. Species with high carbon assimilation rate, nutrient concentration and hydraulic conductivity had high recruitment rates. Leaf turgor loss point was unrelated to plant demography. Principal component analysis revealed that species with quick resource acquisition rates had high rates of growth and recruitment. Our results illustrate that the correlations among tree demographic properties were weak in this subtropical forest with monsoonal climate. Most notably, against expectations, there was no observed trade‐off between growth and mortality. Individual functional traits explained up to 27% of each demographic rate. Variation in recruitment rate was aligned with traits indexing the leaf economic spectrum and also plant hydraulic variation. A better understanding of the role of disturbances on trait–demography relationships would help build a deeper and more nuanced understanding of the ecology of subtropical monsoon forests. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.